Review of Sharia Perspective of Online Forex and Gold Trading Through MetaTrader 4 and MetaTrader 5 Platforms at Futures Brokers in Indonesia - Prasetya, Ilham; Fadila, Nisa Rahma (International Journal of Islamic Finance, 2025)
Background: The COVID-19 pandemic significantly impacted society’s economy. Various industry sectors stopped operating, which resulted in widespread layoffs. As a result, society tends to make online financial transactions, particularly with forex and gold. Objectives: This study examines Islamic law's perspective on online forex and gold futures trading, which is increasingly popular among the public. Novelty: Academic literature specifically conducting a juridical deconstruction (takyif fiqh) of the 'rolling contracts' offered in Indonesia and identifying them as Contracts for Difference (CFDs) remains scarce. A 2021 study noted that "no legal and jurisprudential study has been conducted over this new trade", and a 2024 thesis confirmed a legal vacuum in Indonesia as existing fatwas are considered "not relevant". This research fills this critical gap by providing a precise analysis of these specific derivative instruments, moving beyond the generalized discussions prevalent in current literature. Research Methodology/ Design: The research method used is qualitative analysis with a normative juridical approach. It examines primary Islamic law sources such as the Qur'an, Hadith, scholars' opinions, and literature related to futures trading. Findings: The study results show that online gold futures trading contains several fundamental problems from a Sharia perspective. The first is the ambiguity of the transaction object (gharar). Second, the margin trading and short-selling mechanism allows transactions without full ownership of the commodity. Third, the zero-sum system contradicts the principle of justice in Islamic law. Fourth, there is an element of usury through swap fees when the trading position passes midnight. Fifth, the magnitude of the element of speculation (maysir) in this activity. It can be concluded that the practice of trading gold futures online in its current form does not meet sharia principles. Implication: This study's results are expected to be a reference for policymakers and stakeholders, helping them better socialize and control both instruments.